Translation and psychometric properties evaluation of the engagement in meaningful activities survey (EMAS) - Sumaryanto, Eko, author; Eakman, Aaron, advisor; Persch, Andy, committee member; Kwiatkowski, Lynn, committee member; Dik, Bryan, committee member (Colorado State University. Libraries, 2025)
Meaningful activity is a construct that is core to occupational therapy and related disciplines. The construct contributes a profound influence on people's health, quality of life, and well-being. However, the number of meaningful activity measures in languages other than English remains low. Thus, we translated, adapted, and then examined the validity of the engagement in meaningful activities survey in Bahasa Indonesia (EMAS-BI). In this study, we followed the principles of good practice for the translation and cultural adaptation (TCA) process for patient-reported outcomes. We employed classical theory (factor analysis and convergent validity) to evaluate the psychometric properties of the EMAS-BI and modern test theories (Rasch Rating Scale Model) to the dataset collected using Japanese version of EMAS (EMAS-J) and EMAS-BI. In this dissertation, we employed classical and modern test theories to evaluate the psychometric properties of the EMAS after being adapted and translated. For this reason, we involved 5 translation team members and 6 college students to run a TCA study in Indonesia. Then, we administered EMAS-BI to 1254 college students from Indonesia to examine the psychometric qualities of the translated EMAS. We also ran Rasch Rating Scale Model analysis after adding 369 samples from Japanese college students into the dataset from Indonesia. The results from factor analysis, convergent validity, and Rasch rating scale model provided evidence that EMAS has psychometric qualities that are satisfactory, indicating validity and reliability in measuring meaningful activity construct across different cultures and languages. Conducting a study in a different culture and language helps us to better understand the global construct of meaningful activity. A valid measure will enable us to further explore the interconnection of meaningful activity and well-being aspects in the Indonesian context. Also, developing EMAS in Bahasa Indonesia will provide equal access to the best assessment resources. Besides, a valid measurement tool is necessary to improve the intervention quality provided by Indonesian occupational therapists and the allied professions.
Keywords: factor analysis; occupational therapy; Rasch analysis; meaningful activities; cross-culture; psychometric evaluation